2019
DOI: 10.1007/s13524-019-00762-w
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Concurrency and Contraceptive Use Among Young Adult Women

Abstract: Leveraging 2.5 years of weekly data from the Relationship Dynamics and Social Life Study, we investigate the relationship between young women's sexual concurrency and their contraceptive behavior. Specifically, we (1) examine whether young women changed their contraceptive use when switching from one to multiple concurrent sexual partners in the same week; (2) explore the uniformity of contraceptive responses to concurrency across relationship context; and (3) compare the contraceptive behaviors of never-concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 76 publications
1
1
0
1
Order By: Relevance
“…Similar observations have been reported from previous studies in Ethiopia and Nigeria [18,24,25]. Another study from Michigan observed use of contraceptives four-fold more by young women during their sexual concurrency [26]. Considering the risk of developing an infection people more likely adopt practices to avoid development of infection.…”
Section: Discussionsupporting
confidence: 88%
“…Similar observations have been reported from previous studies in Ethiopia and Nigeria [18,24,25]. Another study from Michigan observed use of contraceptives four-fold more by young women during their sexual concurrency [26]. Considering the risk of developing an infection people more likely adopt practices to avoid development of infection.…”
Section: Discussionsupporting
confidence: 88%
“…Ações que orientem para a prevenção das IST, com enfoque nas atividades educativas, são destacadas em outros estudos sobre a temática (FRANCISCO et al, 2016;SALES et al, 2016;WEITZMAN;BARBER;KUSUNOKI, 2019). E, ainda, a importância da utilização do preservativo em estratégias capazes de influenciar e mudar os comportamentos de risco, favorecendo um desenvolvimento sexual saudável (ALMEIDA et al, 2017;FITZ;ZUCKER, 2015).…”
Section: Discussionunclassified
“…Senn et al (2009) found that women who thought their partner was nonmonogamous were more consistent condom users than those who believed their partner was monogamous. Weitzman et al (2019) showed that women are also more likely to use condoms when they themselves are nonmonogamous. Women also expect to have less control over sex and contraceptive use when they believe their partner is having sex outside the dyad relative to when they believe that same partner is behaving monogamously (Kusunoki and Barber 2019), but they also tend to perceive the partner as having less desire for pregnancy when they are nonmonogamous (Barber et al 2019).…”
Section: Conflict and Power Imbalancementioning
confidence: 99%